Emotions projected in Michel Temer’s letter (Revista de Estudos da Linguagem, 2024)
This study aims to verify the different projected emotions through the images created by Michel Temer (ethos) and through the feelings aroused in the reader (pathos), in the other words, two argumentative categories used to influence their interlocutors (Deputies, Senators and Brazilian people). In this way, the study based on the theoretical and methodological contribution of the Semiolinguistic Theory of Discourse and we intend to study the strategies and the linguistic resources that have the potential to persuade, to convince, emotionally touch the reader through words, and expressions used in the text, in addition the image created of his person as a competent politician to be in the position that he occupies. As a result, we have a letter in which the author uses the ethos of victim and virtue with high frequency and privileges the strategy of evaluation and words that can provoke emotions as pathemic strategies in order to sensibilize his readers.